2007
DOI: 10.1002/jez.b.21187
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish dentition in comparative context

Abstract: Studies of the zebrafish (Danio rerio) promise to contribute much to an understanding of the developmental genetic mechanisms underlying diversification of the vertebrate dentition. Tooth development, structure, and replacement in the zebrafish largely reflect the primitive condition of jawed vertebrates, providing a basis for comparison with features of the more extensively studied mammalian dentition. A distinctive derived feature of the zebrafish dentition is restriction of teeth to a single pair of pharyng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
116
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(120 citation statements)
references
References 202 publications
(187 reference statements)
3
116
0
1
Order By: Relevance
“…The oral region of zebrafish larvae expresses the transcription factor pitx2, a marker of tooth-competent epithelium, but lacks the expression of markers of the dental placode, the earliest morphologically visible sign of tooth development (12,21). We found that arrest of pharyngeal tooth development in nkt mutant homozygotes resembles that found in the wild-type oral region.…”
Section: Loss Of Eda Function In the Zebrafish Pharyngeal Dentition Pmentioning
confidence: 47%
See 2 more Smart Citations
“…The oral region of zebrafish larvae expresses the transcription factor pitx2, a marker of tooth-competent epithelium, but lacks the expression of markers of the dental placode, the earliest morphologically visible sign of tooth development (12,21). We found that arrest of pharyngeal tooth development in nkt mutant homozygotes resembles that found in the wild-type oral region.…”
Section: Loss Of Eda Function In the Zebrafish Pharyngeal Dentition Pmentioning
confidence: 47%
“…Teeth in this group were lost from the entire mouth cavity and upper pharynx at least 50 million y ago and remain only on the fifth ceratobranchial bones of the lower posterior pharynx (Fig. 1A), where they serve the function of mechanical processing of food, especially by chewing (11,12). Such reduction of dentition is thought to have evolved as an adaptation to suction feeding in bottom deposits (11,13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The zebrafish (Danio rerio) is a highly derived Teleost species of the order Cypriniformes and over the past 30 years has become the top fish developmental model owing to its transparency during embryogenesis, the ease of vast embryo production and the development of genomic tools. The zebrafish has become a useful model for tooth development and manipulation [8] however the tiny teeth of zebrafish and teeth in all Cypriniformes are confined to the back of the gill arches, embedded deep within the pharyngeal cavity, with oral teeth in this order having been lost approximately 50 million years ago [9].…”
Section: Introductionmentioning
confidence: 99%
“…Teleost fish including zebrafish often have diversified alleles homologous to a mammalian counterpart supposedly due to ancient whole gene duplications (Stock, 2007, Wittbrodt et al, 1998. Blast searches indicate that there are two alleles (EU267178 and our AB297803) in the zebrafish genome homologous to mammalian pcdh18.…”
Section: Discussionmentioning
confidence: 99%